Design and Evaluation of a Digital Transformation Canvas for SME - Neidlinger, Lukas; Jung, Jürgen (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Due to the rapid evolution of digital technologies and associated business benefits, companies are forced to adapt their business models and operational processes. However, especially small and medium-sized companies perceive a significant risk imposed by a digital transformation as they lack digital capabilities and necessary resources. Overwhelmed by heavy-weight frameworks and methods, such companies rather need a simple approach like a business model canvas for digital transformation. The objective of the research presented in the paper at hand is to present reesarch in progress on the design and validation of a digital transformation canvas for small and medium-sized enterprises. It has been developed together with the Chamber of Industry and Commerce in Offenbach (Germany) as well as two member companies.